STRATEGI PENGEMBANGAN DESA WISATA DALAM UPAYA MENINGKATKAN KEMANDIRIAN DESA - Lustina Fajar Prastiwi; Inayati Nuraini Dwiputri; Annisya' (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
The tourism village development strategy is essential for villages that still need natural tourism. This is intended so that the developed tourism villages can survive and continue to increase over time. If the Tourism Village is adequately managed, it is hoped that it will help increase the income of the Village and especially the managing community members and the community around the Tourism Village. The objectives of the Community Partnership Program activities in the Desa Wisata Tani’s Community are 1) Increasing community participation in the Farmer Tourism Village area and 2) Increasing the effectiveness of tourism village activities through community participation. The method of this service activity is 1) program planning activities, 2) implementation or implementation activities, 3) and supervision. This activity succeeded in bringing together the community around the tourist village and the tourism awareness group (Pokdarwis) Regul, which manages Wisata Tani Betet (WTB). The results of this activity are the formation of management and organizational structure, the implementation of farmer festival activities, and the availability of tourist village facilities and infrastructure to a good monitoring system.  ---   Strategi pengembangan Desa Wisata sangat penting bagi desa yang tidak mempunyai wisata alami. Hal ini ditujukan agar Desa Wisata yang dikembangkan dapat bertahan dan terus meningkat seiring dengan berjalannya waktu. Jika Desa Wisata dikelola dengan baik, maka diharapkan akan membantu meningkatkkan pendapatan Desa dan terutama warga masyarakat pengelola serta masyarakat sekitar Desa Wisata. Tujuan diadakaanya kegiatan Program Kemitraan Masyarakat pada Masyarakat Desa Wisata Tani adalah : 1) Meningkatkan partisipasi masyarakat kawasan Desa Wisata Tani, 2) Meningkatkan efektifitas kegiatan desa wisata melalui partipasi masyarakat. Metode kegiatan pengabdian ini adalah 1) kegiatan perencanaan program, 2) kegiatan pelaksanaan atau implementasi, 3) pengawasan. Kegiatan ini berhasil menghimpun masyarakat sekitar desa wisata dan kelompok sadar wisata (Pokdarwis) Regul, yang mengelola Wisata Tani Betet (WTB). Hasil dari kegiatan ini adalah terbentuknya pengurus dan struktur organisasi, terselenggaranya kegiatan festival tani, tersedianya sarana dan prasarana desa wisata hingga sistem pengawasan yang baik.